Improve energy efficiency in the aviation industry by projecting use of technology parallel computing - Zilinka, V.; Shkvar, E. (Energy and Automation, 2015)
Mathematical modeling of flow compartment finite span wing by parallelization on high performance computer cluster architecture. The results of calculation of integrated aerodynamic characteristics of the wing compartment and effectiveness acceleration calculation based on the number of elements of finite volume mesh and the number of processor cores involved.